Natural Killer Cells Prevent the Formation of Teratomas Derived From Human Induced Pluripotent Stem Cells - Benabdallah, Basma; Désaulniers-Langevin, Cynthia; Colas, Chloé; Li, Yuanyi; Rousseau, Guy; Guimond, Jean V.; Haddad, Elie; Beauséjour, Christian (Frontiers in Immunology, 2019)
The safe utilization of induced pluripotent stem cell-derivatives in clinic is tributary to the complete elimination of the risk of forming teratomas after transplantation. The extent by which such a risk exists in immune competent hosts is mostly unknown. Here, using humanized mice reconstituted with fetal hematopoietic stem cells and autologous thymus tissue (Hu-BLT) or following the adoptive transfer of peripheral blood mononuclear cells (PBMCs) (Hu-AT), we evaluated the capacity of immune cells to prevent or eliminate teratomas derived from human induced pluripotent stem cells (hiPSCs). Our results showed that the injection of hiPSCs failed to form teratomas in Hu-AT mice reconstituted with allogeneic or autologous PBMCs or purified NK cells alone. However, teratomas were observed in Hu-AT mice reconstituted with autologous PBMCs depleted from NK cells. In line with these results, Hu-BLT which do not have functional NK cells could not prevent the growth of teratomas. Finally, we found that established teratomas were not targeted by NK cells and instead were efficiently rejected by allogeneic but not autologous T cells in Hu-AT mice. Overall, our findings suggest that autologous hiPSC-derived therapies are unlikely to form teratomas in the presence of NK cells.